Hepatoprotective effects of bioactive compounds from traditional herb Tulsi (Ocimum sanctum Linn) against galactosamine-induced hepatotoxicity in rats - Kamel, Fatemah O.; Karim, Shahid; Bafail, Duaa Abdullah Omer; Aldawsari, Hibah Mubarak; Kotta, Sabna; Ilyas, U. K. (Frontiers in Pharmacology, 2023)
Ocimum sanctum L. (Tulsi; Family: libiaceae), also known as "The Queen of herbs" or "Holy Basil," is an omnipresent, multipurpose plant that has been used in folk medicine of many countries as a remedy against several pathological conditions, including anticancer, antidiabetic, cardio-protective, antispasmodic, diaphoretic, and adaptogenic actions. This study aims to assess Ocimum sanctum L.'s hepatoprotective potential against galactosamine-induced toxicity, as well as investigate bioactive compounds in each extract and identify serum metabolites. Hepatotoxicity was induced albino adult rats by intra-peritoneal injection of galactosamine (400 mg/kg). The quantified hydroalcoholic and alcoholic extract of Ocimum sanctum L (100 and 200 mg/kg body weight/day) were compared for evaluation of hepatoprotective potential, which were assessed in terms of reduction in histological damage, change in serum enzymes such as AST, ALT, ALP and increase TBARS. We evaluated the hepatoprotective activity of various fractions of hydroalcoholic extracts based on the polarity and investigated the activity at each phase in-vitro to determine how they affected the toxicity of CCL4 (40mM) toward Chang liver cells. The ethyl acetate fraction of the selected plants had higher hepatoprotective activity than the other fractions, so it was used in vacuum liquid chromatography (VLC). The ethyl acetate fraction contains high amounts of rutin (0.34 % w/w), ellagic acid (2.32% w/w), kaempferol (0.017% w/w), caffeic acid (0.005%w/w), quercetin (0.038%w/w), and epicatechin (0.057% w/w) which are responsible for hepatoprotection. In comparison to standard silymarin, isolated bioactive molecules displayed the most significant hepatoprotective activity in Chang liver cells treated to CCl4 toxicity. The significant high hepatoprotection provided by standard silymarin ranged from 77.6% at 100 g/ml to 83.95% at 200 g/ml, purified ellagic acid ranged from 70% at 100 g/ml to 81.33% at 200 g/ml, purified rutin ranged from 63.4% at 100 g/ml to 76.34% at 200 purified quercetin ranged from 54.33% at 100µg/ml to 60.64% at 200 µg/ml, purified epicatechin ranged from 53.22% at 100µg/ml to 65.6% at 200 µg/ml, and purified kaempferol ranged from 52.17% at 100µg/ml to 60.34% at 200 µg/ml. These findings suggest that the bioactive compounds in Ocimum sanctum L. have significant protective effects against galactosamine-induced hepatotoxicity.